Aspects of War in Medieval French Occasional Verse - Tyson, Diana B. (Nottingham Medieval Studies, 2015)
Abstract This paper surveys the views on and the effects of war as expressed in medieval French verse written for or arising from specific occasions. The poems cited include epitaphs, encomia, crusading songs, siege narratives, protest and political verse, victory celebrations, and folk songs, both insular and continental. Many of them voice despair at the violence inflicted on civilian populations but there is also the glorification of exploits of war and worship of military leaders. The lengths of the poems vary greatly, as do their dates - from the late twelfth to the middle of the sixteenth centuries. The need for further work on this neglected part of Old French literature is emphasized.